A town-library - Brinkman, Henry W. (My University, 1907)
Introduction: Specifications of material and labor required for the erection of a library building to be built in the City of………………, State of…………., for the citizens thereof, who will be represented by a Library Board or Agent, transacting business and the building operations for them. Said library is to be built according to plans and specifications prepared for the same by Henry W. Brinkman, Architect, Manhattan, Kansas. These plans, etc., referred to herein, consist of the following drawings, all drawn to a scale of 1/8" to one foot, except when otherwise stated. No. 1…..Plate of Basement. No. 2….." " First Floor. No. 3….." " Second Floor. No. 4….." " Roof & Attic.No. 5….." " Front Elevation. No. 6….." " Side Elevation. No. 7….." " Rear Elevation. No. 8….." " Cross Section.No. 9….." " Detail of Bases & Casings. No. 10...." " " "Columns & Cornice. The drawings, together with these specifications and oral dictations from the Architect or Superintendent, are intended to be sufficient for the necessary guidance to the furnishing of material to be used, and the required work to be done in the construction and completion of the aforesaid building.
Citation: Brinkman, Henry W. A town-library. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Town Library; Construction; Architecture; Manhattan, Kansas; Theses